Foreign body in vagina: a cause of persistent vaginal discharge in children - Pallavee, P.; Samal, Sunita; Sabita, P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Vulvovaginitis and vaginal discharge in pediatric patients, while not uncommon, is commonly believed to be due to such causes as absence of the protective effect on the vaginal mucosa. However, other causes need also to be kept in mind. We report a case of chronic vaginal discharge in a 5 yr old, who had retained a foreign body in her vagina for 6-7 months.